Informant‐based report of cognitive decline correlates with age‐adjusted hippocampal volume in mild cognitive impairment and Alzheimer's dementia?: Neuropsychiatry and behavioral neurology/Mild cognitive impairment/Early symptomatic disease. (7th December 2020) - Sabbagh, Marwan Noel; Miller, Justin; Wint, Dylan
Abstract: Background: Informant‐based measures can be effective screening tools for cognitive impairment. The Alzheimer's Questionnaire (AQ; Sabbagh et al., 2010) is a subjective, informant‐based measure that captures five cognitive domains associated with Alzheimer's disease (AD). The AQ detects amnestic mild cognitive impairment (aMCI) and Alzheimer‐type dementia with high sensitivity and specificity, and has also been shown to predict amyloid burden. We hypothesize that a higher AQ score (greater functional impairment) correlates with lower hippocampal volumes. Method: Retrospective chart review of 131 clinically referred patients with clinical diagnoses of aMCI or mild dementia due to AD was conducted. Diagnostic status (clinical diagnosis made by a neurologist), NeuroQuant measured MRI brain with percentile rank hippocampal volume, Montreal Cognitive Assessment (MoCA) total, AQ‐Total score, and demographic variables were extracted from medical records. Spearman correlation was used to assess the relationship between hippocampal volume and AQ‐Total. As the AQ was used as a factor in assigning diagnostic status, thus the relationship between the AQ and diagnostic status was excluded from analyses. Result: The analyzed sample was 53% female with a mean of 73.96±10.48 years of age and 14.74±3.51 years of education. Sample means for the MoCA and AQ score were 22.16±4.39 and 10.62±5.29, respectively. Correlation between AQ score and HC volume (as reported as percentile) revealed an inverse relationship, such that higher AQ scores were associated with smaller hippocampal volumes (r =‐0.40 (95% CI ‐0.54 to ‐0.24), p<0.0001). Conclusion: In a mixed‐clinical sample of patients presenting to an outpatient memory disorders center, higher endorsements of functional impairments by caregivers were significantly associated with smaller hippocampal volumes. When used in conjunction with other available measures, these findings further support the role of the AQ in clinical decision‐making, and demonstrate an additional relationship with established AD biomarker outcomes with volumetric MRI.